(untitled) (Medico Legal Update, 2019)
The purpose of this study was to compare the changes and determine the effect of AR program and therapist instructions on exercise according to proprioception, stability, blood pressure and ROM. This study consisted of a total of 42 subjects; 22 healthy men and 20 healthy women with no orthopedic cardiovascular disease. The subjects performed proprioceptive exercise in various postures, and the Paired T-test was used to confirm the difference in change between the AR program group and the group trained under the therapist instruction. Independent T-test method was used to confirm the difference between the two groups. There were no ROM changes in both groups and the overall proprioception. The balance of the lower limb significantly increased but contrarily, the blood pressure significantly decreased. There were no significant differences between the two groups. The use of AR program and therapist’s instructions has a positive effect on proprioception, balance and affects blood pressure. There were no significant differences between them. Therefore, it is thought that the AR program can be a good alternative as a therapeutic tool in clinical practice.